Medical image fusion using enhanced cross-visual cortex model based on artificial selection and impulse-coupled neural network. (February 2023) - Xu, Wanni; Fu, You-Lei; Xu, Huasen; Wong, Kelvin K.L.
Highlights: Cross-cortical improved model for medical image fusion based on impulse-coupled neural networks and artificial selection techniques. ICM was enhanced with NSCT and applied to the fusion of medical images. CT/MRI medical images of healthy brain tissue, large numbers of cerebral infarcts and acute strokes were combined using image fusion. Advantages of outstanding edge information, high contrast and brightness. Abstract: Objective: The traditional ICM is widely used in applications, such as image edge detection and image segmentation. However, several model parameters must be set, which tend to lead to reduced accuracy and increased cost. As medical images have more complex edges, contours and details, more suitable combinatorial algorithms are needed to handle the pathological diagnosis of multiple cerebral infarcts and acute strokes, resulting in the findings being more applicable, as well as having good clinical value. Methods: To better solve the medical image fusion and diagnosis problems, this paper introduces the image fusion algorithm based on the combination of NSCT and improved ICM and proposes low-frequency, sub-band fusion rules and high-frequency sub-band fusion rules. The above method is applied to the fusion of CT/MRI images, subsequently, three other fusion algorithms, including NSCT-SF-PCNN, NSCT-SR-PCNN and Adaptive-PCNN are compared, and the simulation results of image fusion are analyzed and validated. Results: According to the experimental findings, the suggested algorithm performs better than other fusion algorithms in terms of five objective evaluation metrics or subjective evaluation. The NSCT transform and the improved ICM were combined, and the outcomes were evaluated against those of other fusion algorithms. The CT/MRI medical images of healthy brain tissue, numerous cerebral infarcts and acute strokes were combined using this technique. Conclusion: Medical image fusion using Adaptive-PCNN produces satisfactory results, not only in relation to improved image clarity but also in terms of outstanding edge information, high contrast and brightness.